Impact of brine composition on the selective removal of Ca2+ and Mg2+ via carbonate formation - Jiwon Myung; Won Yong Choi; Seojin Oh; Kyumin Jang; Eunsil Kim; Sangyup Lee; Jinwon Park; Dongwook Lee (Chemical Engineering Journal, 2025)

Sustainable conversion of oyster shell waste into high-purity calcium carbonate via CO2 mineralization - Kyumin Jang; Ikram Moulay; Dongwook Lee; Jiwon Myung; Seojin Oh; Seok-Hwi Kim; Won Yong Choi; Jinwon Park (Journal of Environmental Chemical Engineering, 2025)

Synthesis of seawater-derived superhydrophobic calcium carbonate via CO2 mineralization by utilizing L-Arginine/L-Lysine oleate-based self-assembly structures - Sungsoo Lee; Eunsil Kim; Dongwook Lee; Kyumin Jang; Jinwon Park; Won Yong Choi (Chemical Engineering Journal, 2024)

Advancing seawater-based mineral carbonation: Exploring novel pathways for enhanced carbonation efficiency and control of carbonate polymorphism and size - Dongwook Lee; Kyumin Jang; Eunsil Kim; Won Yong Choi; Jinwon Park (Desalination, 2024)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.